(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
The article is about supporting the future teacher’s actions in the direction of his interests in the development of his creative abilities, setting clear goals and tasks for them, and about his internal motivation, which expresses his interest and interest in his profession, and about the development of the field of will. raised The author also spoke about the issues of developing the creative activity of pedagogues